Technostress and time spent online. A cross-cultural comparison for teachers and students - Cazan, Ana-Maria; David, Laura Teodora; Truța, Camelia; Maican, Cătălin Ioan; Henter, Ramona; Năstasă, Laura Elena; Nummela, Niko; Vesterinen, Olli; Rosnes, Arne Morten; Tungland, Tobias; Gudevold, Eirin; Digernes, Mari; et al. (Frontiers in Psychology, 2024)
Research shows that ICT is beneficial for academics and students, aiding in overcoming distance barriers, streamlining administration, and improving teaching and learning processes. However, the negative impact of technology, particularly technostress, are garnering attention. In the context of the concerns about technostress among higher education institutions (HEI), the aim of the study is to analyse the technostress creators and inhibitors for university teachers and students in different European countries. The topical concept of digital well-being is seen as "a subjective individual experience of optimal balance between the benefits and drawbacks obtained from mobile connectivity, focusing on the personal perception of what amount of time spent using technology is optimal so that well-being is preserved. To explore specific aspects related to use of technology, two parallel online surveys for academics (N = 446) and students (N = 660) from four European countries (Romania, Germany, Norway, and Finland) were conducted between November 2022 -January 2023. The surveys included the Technostress scale and the Technostress Inhibitors Scale, the Technology self-efficacy Scale, and a questionnaire focusing on socio-demographic aspects, work experience, academic field, dimensions related to the actual use of technology and participants perception on the optimal use of technology for work, learning or personal tasks, in terms of the period of day/week and amount of time spent. We also inquired about the social support given and received when using technology and the formal and informal rules, expectations, policies, punishments, and rewards regarding the use of technology. The findings suggest that the perceived optimal use of technology is significantly lower than the actual use for all the contexts. Overuse of technology was associated with technostress. Our results also showed that technology self-efficacy and social support from colleagues and teachers are negatively associated with technostress. Country differences regarding technostress and time spent online were also observed. Despite the needed caution in interpreting the results because of the unbalanced sample size across countries, the results could be used to develop research and support interventions within European countries to promote digital well-being, a better work-life balance with further positive effects on academic satisfaction and work/learning productivity.